Sleep-Related Problems and Associations with Occupational Factors among Home Care Personnel - Lindholm, Maria; Målqvist, Ingela; Alderling, Magnus; Hillert, Lena; Lind, Carl M; Reiman, Arto; Forsman, Mikael (Nordic Journal of Working Life Studies, 2022)
Recent demographic developments in Europe have increased the demand for home care. Working in other people’s home environment is challenging. Home care personnel’s musculoskeletal disorders are common, and care personnel overall often have sleep disturbances. In this study, associations between occupational physical and psychosocial factors and possible sleep-related problems among home care personnel were explored using a questionnaire. The questionnaire was distributed to 19 workplaces in Stockholm County in 2017–2019, and 665 home care personnel answered. Several factors, including job contentment, physical burden of care, client-related burnout, quantitative demands, and pain, were significantly associated with sleep-related problems. The results highlight the need for implementing measures to improve psychosocial and organizational working conditions in home care service.